2022
DOI: 10.1037/men0000401
|View full text |Cite
|
Sign up to set email alerts
|

Conformity to masculine norms and men’s responses to the COVID-19 pandemic.

Abstract: The study examined men’s conformity to masculine norms as related to adherence to Centers for Disease Control and Prevention (CDC) recommendations for mitigating the spread of COVID-19 as well as men’s attitudes toward mask wearing. Five hundred eighty nine participant men, predominantly White and heterosexual, completed the 10–15 min anonymous online survey through Prolific. After controlling for demographics, results indicated that the masculine norms of emotional control and power over women were related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Finally, Mahalik et al (2022) explored whether political ideology moderated the proposed relationship. These authors found that in general, conservative men had more negative attitudes to masks than liberal men.…”
Section: Moderators and Mediatorsmentioning
confidence: 99%
“…Finally, Mahalik et al (2022) explored whether political ideology moderated the proposed relationship. These authors found that in general, conservative men had more negative attitudes to masks than liberal men.…”
Section: Moderators and Mediatorsmentioning
confidence: 99%
“…More specifically, we anticipate that conformity to the masculine norms of emotional control and self-reliance will moderate those relationships given that these norms were “consistently and unfavorably associated with mental health-related outcomes” (Wong et al, 2017, p. 89), as well as associated with health risk behaviors and attitudes (Mahalik et al, 2022). We posit that the relationship between depressive symptoms and health beliefs, as well as the relationship between health beliefs and heart-healthy behaviors, may be moderated by emotional control and self-reliance.…”
Section: The Head and The Heart: Psychological Factors In Cardiac Hea...mentioning
confidence: 99%
“…N = 459. Minimum and maximum values are indicated in parentheses for the following abbreviations: health behaviors (11, 48) = heart-healthy behaviors; depressive symptoms (0, 51) = Center for Epidemiologic Studies-Depression Scale; benefits (16, 48) = perceived benefits of heart-healthy behaviors; barriers(8, 43) = perceived barriers to heart-healthy behaviors; emotional control (1, 6) = conformity to emotional control masculinity norm; self-reliance (1, 6) = conformity to self-reliance masculinity norm. * p < .05.…”
mentioning
confidence: 99%
“…Not only are masculinity norms an important sociological phenomenon that affects society as a whole, but conformity to those norms is of particular interest to health practitioners due to its correlation. For example, studies have linked conformity to masculinity with important health risk behaviors (e.g., Mahalik et al, 2007; Mahalik et al, 2022a) and mental health outcomes such as depression, substance use, negative social functioning, body image problems, stress, and reluctance to seek help (see Wong et al, 2017 for a meta-analysis). Some elements of conformity to masculinity norms like not expressing one’s emotions and avoiding affectionate behaviors are reported to be especially important when predicting negative mental health outcomes.…”
Section: Masculinity Normsmentioning
confidence: 99%